2008
DOI: 10.1017/s1368980007000407
|View full text |Cite
|
Sign up to set email alerts
|

Hunger and health among undocumented Mexican migrants in a US urban area

Abstract: Objectives: To measure the occurrence and correlates of hunger and to evaluate the association between hunger and three health indicators among undocumented Mexican immigrants. Design: Non-probability cross-sectional sample. Setting: Neighbourhoods within New York City. Subjects: Four hundred and thirty-one undocumented Mexican immigrants living in the USA. Results: Hunger was indicated by approximately 28% of respondents. In a multivariate model, working as a day labourer was associated with hunger (odds rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 35 publications
1
33
1
5
Order By: Relevance
“…Acculturative stress was identified as common among immigrants with limited English proficiency, deficits in stress-coping resources, and those reporting high family cohesion (Miranda & Matheny, 2000;Sanchez, Dillon, Ruffin, & De La Rosa, 2012). Also, longer time lived in the United States was associated with increased mental health distress as measured by self-rated health questions adapted from the Behavioral Risk Factor Surveillance System and the National Health and Nutrition Examination Survey (Hadley et al, 2008). Additionally, in a study of Mexican immigrants in which most were undocumented, marital conflict and separation from family were associated with interpersonal distress as measured by the Mental Health Risk Factor (MHRF) Survey, an instrument developed by the author to assess mental health distress among Latinos (Santos, Bohon, & S anchezSosa, 1998).…”
Section: Findings From Quantitative Studies: Mental Health Outcomes Amentioning
confidence: 99%
See 1 more Smart Citation
“…Acculturative stress was identified as common among immigrants with limited English proficiency, deficits in stress-coping resources, and those reporting high family cohesion (Miranda & Matheny, 2000;Sanchez, Dillon, Ruffin, & De La Rosa, 2012). Also, longer time lived in the United States was associated with increased mental health distress as measured by self-rated health questions adapted from the Behavioral Risk Factor Surveillance System and the National Health and Nutrition Examination Survey (Hadley et al, 2008). Additionally, in a study of Mexican immigrants in which most were undocumented, marital conflict and separation from family were associated with interpersonal distress as measured by the Mental Health Risk Factor (MHRF) Survey, an instrument developed by the author to assess mental health distress among Latinos (Santos, Bohon, & S anchezSosa, 1998).…”
Section: Findings From Quantitative Studies: Mental Health Outcomes Amentioning
confidence: 99%
“…In this study, demanding work schedules, limited financial resources, and limited access to documentation were identified as primary reasons limiting UIs' ability to bring their children to the United States. Regarding limited resources, one study identified food insecurity/hunger as a common stressor among UIs, and a significant predictor of poor mental and physical health using self-rated health questions adapted from national surveys (Hadley et al, 2008).…”
Section: Findings From Quantitative Studies: Mental Health Outcomes Amentioning
confidence: 99%
“…1 They maneuver within, between, and outside a host of forces and structures that take physical and emotional toll and affect their access to health and social services. Their unsanctified position of illegitimacy affects their decisions and practices in addressing personal dilemmas and bodily afflictions (Hadley et al 2008;Wasem and Richardson 2002), while they also valiantly attempt to resist the imposed stigmatized social category to which they have been shunted ( Barriga 1997).…”
mentioning
confidence: 99%
“…Legally ineligible to work and often to even drive, undocumented immigrants are limited to low-wage, often unstable work, and common experiences of wage theft (Bernhardt et al 2009; Hall and Greenman 2015; Hall, Greenman and Farkas 2010). Those conditions in turn constrain housing options, contributing to overcrowding, food insecurity, and high levels of stress, all of which may in turn lead to adverse health outcomes for both adults and children (Hadley et al 2008; Ortega et al 2009; Yoshikawa 2011). …”
Section: Migration Control Civic Stratification and Health Carementioning
confidence: 99%